THINKING OF THE SAFETY APPLICATION OF TCM BY YOU GU WU YUN, A CHINESE ANCIENT MEDICINE APPLICATION PRINCIPLE - Peng, Wei; Gao, Fei; Jiang, Yan-Ping; Yang, Huan; Gan, Yan-Xiong; Lu, Jun-Rong; Fu, Chao-Mei; Li, Peng (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: You Gu Wu Yun (有故无殒), a Chinese ancient medicine application principle, has played an important role in TraditionalChinese Medicine (TCM) clinical practice so far.Materials and Methods: It emphasized that disease, medicine and treatment method were interconnecting and the relationship among thesethree aspects should be handled reasonably. The major factors (including organism status, medicine source, medicine processing, compatibilityof medicines, dose and course, dosage form) under the three aspects which have a more important and direct influence on the medicine clinicaleffect should be considered seriously in the TCM application.Results: However, it was analyzed that most of side effects of TCM may be due to the incorrect application, which violated this principle to acertain degree. In order to help people to understand the safety and toxicity of TCM objectively and provide a rational guidance for the safe andeffective application of TCM, we will introduce the concept of You Gu Wu Yun and discuss these factors having influence on medicine in thisreview. An example will be shown in order to clarify how these factors work in medicine.Conclusions: As a unique medical system, TCM has its own theoretical basis and treatment principle. It stresses syndrome